ChemInform Abstract: A Highly Active Bifunctional Iridium Complex with an Alcohol/Alkoxide‐Tethered N‐Heterocyclic Carbene for Alkylation of Amines with Alcohols. Issue 14 (20th March 2013) - Bartoszewicz, Agnieszka; Marcos, Rocio; Sahoo, Suman; Inge, A. Ken; Zou, Xiaodong; Martin‐Matute, Belen
Abstract A series of novel iridium complexes possessing chelating [NHC‐alcohol] ligands is prepared.